Strawberry-fortified Yogurt: Production, Sensory, Antioxidant Activity Test, and Model for Practicum - Florentina Maria Titin Supriyanti; Dida Roslina; Z. Zackiyah; Islah Hanifa (Universitas Pendidikan Indonesia, 2022)
This study aims to produce as well as analyze the sensory and antioxidant activity of fortified strawberry yogurt with cryoconcentration and pasteurization preparation methods. The results for the sensory test of strawberry fortified yogurt showed that the pasteurized yogurt is the best for taste and aroma because the use of heat when pasteurizing releases the aroma from strawberries. Reducing the water content using this method allows the strawberry flavor more concentrated. The cryoconcentration method allows the texture and color to be better than other methods. This is influenced by the use of low temperatures in the cryoconcentration method to maintain the anthocyanin content in strawberries which acts as a red pigment. The greater concentration of fortificants added results in higher antioxidant activity gained. Based on the IC100 value, the fortification of strawberries with the cryoconcentration method was significantly different from the pasteurization method in increasing the antioxidant activity of strawberry-fortified yogurt. The benefit of this research is to process milk into yogurt. Thus, it can be consumed by consumers with lactose intolerant sufferers. The addition of strawberries increases the antioxidants to prevent degenerative diseases. In addition, due to its simply design and production, this study is possibly used as a model in the practicum class.